EKSTRAK DAUN KEMANGI SEBAGAI OBAT KUMUR TERHADAP pH SALIVA - azzahra siti, rosinta (THERA-DENT (jurnal terapis gigi dan mulut), 2023)
Background: Dental caries or cavities are caused by one of them being an abnormal salivary pH. Prevention efforts that can be done is by gargling. The use of herbal ingredients such as basil leaves can be used as a mouthwash. Basil leaves contain flavonoids and apigenin which have antibacterial effectiveness and have a distinctive aroma and taste of basil. Gargling basil leaf extract is one way to prevent dental caries. Purpose: the purpose of this study was to determine whether there was an effect of basil leaf extract as a mouthwash on salivary pH. Research method: this type of research is quantitative research. The method used is quasi- experimental. The sampling method is Simple Random Sampling, using 40 students from Baburridho Junior High School Jakarta, using a pH meter to determine the salivary pH criteria. This study uses tabulation and frequency distribution. Results: The results of this study revealed that there was a change in salivary pH after gargling with basil leaf extract, which was neutral from 6.6 to 7.0 and alkaline from 7.3 to 7.5. Conclusion: there is an effect of gargling basil leaf extract on salivary pH which tends to the alkaline criteria. It is recommended for students to rinse their mouth using boiled water with basil leaf extract as an alternative to prevent caries.